Pengaruh Komunikasi Organisasi dan Budaya Organisasi Terhadap Kinerja Pegawai Bagian Sosial Sekretariat Daerah Kabupaten Lahat (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
The problems formulated from this study is whether organizational communication and organizational culture have influence on the performance of employees Social Part of Lahat District Secretariat. While the analytical tool used is multiple linear regression. The results show the value of the coefficient of determination (R2) of 0.446. This means that the variable organizational communication and organizational culture can explain the performance variable (Y) was 44.6%, while the remaining 55.4% explained by other variables not included in the model of this research. Furthermore, calculation of F obtained a value of 30,995, while a significant Ftable 3.9604 at α = 0.05, it can be seen that F count> F table. This means that Ho is rejected and Ha accepted, meaning that there is a significant influence between independent variables (organizational communication and organizational culture) to the dependent variable (employee performance) at the Secretariat of the Social Section of Lahat Regency. Furthermore, the results of the t test calculations can be in the know tcount of organizational communication variables (X1) is equal to 3,429 and ttable of 1.6649 (t count> t table) which means testing the hypothesis Ho is rejected and Ha accepted. This suggests that partially with LOS (level of significance) α = 0.05 there is the influence of independent variables on the dependent variable, whereas for organizational culture (X2) and 2,772 tcount ttable 1.6649 with LOS (level of significance) α = 0.05. In other words t count> t table means testing Ho is rejected.